The austerity bargain and the social self: conceptual clarity surrounding health cutbacks - Buchanan, David A. (Nursing philosophy, 2013)
As necessary austerity measures make major inroads into western health services, this paper investigates the philology of austerity and finds that there are two subtly similar yet importantly different derivations from the Latin and the Greek. The Latin austerus is an abstract term meaning dry, harsh, sour; whereas the Greek austeros has a more embodied and literal meaning of making the tongue dry. What seems an initially subtle difference between the metaphorical and the metonymic plays out as involving seriously different outcomes between harsh economic measures and the literal effects on the people suffering under measures that actually make the tongue dry. The paper argues that between the trope and the literal that which Wittgenstein described as ‘a language game’ ensues wherein the metaphorical through a sleight of grammar is passed off as being real while, the literal effects on real people is downplayed as metaphorical ‘collateral damage’. The paper further argues that within this grammar that forces itself upon us, the game of capital is played out through what the author terms an austerity bargain that is levelled by the financial elites: healthy capitalism equals a healthy society. The paper then examines the six elements of the social determinants of health and what actually contributes to a healthy society. Rather than being under an individual threat of exclusion from what Marx termed a superabundance, the paper considers the irreducible differences between the game of capital's individualism, and, the social determinants of health's social inclusion, legitimization and that which Habermas termed public authentication. The paper concludes that not only do necessary austerity measures need to be critiqued but that they radically undermine what determines a healthy society. It follows also that the social determinants of health, radically undermine the bargain inherent for the privileged few within the game of capital.